Late Paleocene pipe swarm in the Great South – Canterbury Basin (New Zealand). (September 2019) - Bertoni, Claudia; Gan, Yuqian (Philomena); Paganoni, Matteo; Mayer, Jan; Cartwright, Joe; Martin, Joe; Van Rensbergen, Pieter; Wunderlich, Alexander; Clare, Alan
Abstract: We have identified a deeply buried fluid escape pipe province in Cretaceous - late Paleocene sediments of the Great South–Canterbury Basin (NZ). The seismic observations and interpretations point to an unusually vast fossil system of pipes. These features are exceptional in number (>2000 edifices) and appear to have formed from a common root zone. The areal extent of the analysed pipe system (2500 km 2 ) is among the largest systems of fluid expulsion features ever observed in three-dimensional seismic data. The unclustered distribution of the pipes suggests no specific link to faults or buried sedimentary features and, at their maximum vertical development, the pipes are equally distributed above depocentres or structural highs. The majority of pipes terminate at two discrete levels in the late Paleocene. Based on the geometrical relationship of the pipe edifices to the overburden, and the basinal setting of the hosting units, we interpret these horizons as representing the seabed at the time of pipe formation. This interpretation allows us to date the timing of pipe formation as prominently late Paleocene. We envisage that the pipes originated during discrete episodes of fluid venting in this time interval, disrupting the typical progressive basinal compaction-driven pore fluid expulsion. The pipes are associated with biogenic gas expulsion. We discuss their triggers, mechanical processes, and global significance for understanding fluid flow processes in sedimentary basins. Creation of the initial overpressure could be related to in situ biogenic gas generation in the stratigraphic interval coincident with the root zone of the pipes. We hypothesise that the main episode of gas release and pipe formation was associated with a sea-level fall during the contemporaneous late Paleocene Carbon Isotope Maximum. This case study shows a unique example of a preserved Paleogene fluid migration system and highlights how the observation and the interpretation of massive fossil systems of fluid-escape features provides invaluable information in terms of overpressure generation and basin fluid expulsion history. Highlights: Unusually vast fossil system of fluid escape pipes discovered offshore New Zealand. The >2000 pipe edifices formed in the late Paleocene and are at present deeply buried. They are associated to overpressure development linked to biogenic gas generation. Gas release likely associated with late Paleocene Carbon Isotope Maximum sea-level fall.